KEHIDUPAN SOSIAL EKONOMI MASYARAKAT SUKU NIAS DI KORONG TANJUNG BASUNG II KENAGARIAN SUNGAI BULUH KECAMATAN BATANG ANAI KABUPATEN PADANG PARIAMAN 1995-2013 - Sipayung, Ivana - (Pendidikan Sejarah, 2014)
This study discusses the social and economic life of ethnic nias in Korong Tanj ung Basung II. The research problem is formulated as below (a) how early entry process ethnic nias in Koroog Tanjung basung n(b) what is the public relationship between ethnic nias and ethnic Minang in Korong TanjiDlg basung n (c) bowsocial and economic life of ethnic Nias in Koroog TanjiDlg Basung D. This study aims to reveal about socialand economic life of ethnic Nias in Korong Tanjung Basung ll Kenagarian Sungai Bulub in 1995-2013.Thisresearch includes the study of history, therefore the this study follows the historical methods are: (I ) heuristics that searching and collecting information from primary and secondary sources, (2) criticism of sources including internal and external criticism, with tested the authenticity of the source or specified materials, (3) interpretation is an activity of interpreting the data that has been collected, and (4) historiography ie stage presentation of research results in the form of a thesis.The results of the study explained : (I ) the ethnic Nias in Korong Tanjung BasiDlg ii is the ethnic Nias who previousl y lived in Ulakan Tapakis and Kampung Nias in Pariarnan which now changed its name to kampung baru, in 190I they were invited by datuak kasupian to open up the Sungai Bulub that previousl y were shaped jungle . Nias people first inhabited the Sungai Bulub consists of seven families that are Zebua, Hareffa , Dohare, Era-era, Zai, Gea , and Waruwu . (2) the social life of ethnic nias in Korong Tanjung Basung IJ seen from the social relations of ethnic Nias with other tribes such as the Javanese, Batak and Minang in Korong Tanjung Basung IJ Kenagarian Sungai Bulub. The social life of ethnic Nias is also visible harmony in the fields of religious , activities of mutual cooperation, and harmony in marriage ceremonies I custom. (3) economic Hfc of ethnic nias was initially very apprehensive because they live in remote and isolated areas. But since the opening of the entrance to the area in 1995, gradually the economic life of the people of ethnic nias began to improve. Th.is is evident from its abiHty to meet their needs, even the ability to send their children to college.